Tainted milk : breastmilk, feminisms, and the politics of environmental degradation - Boswell-Penc, Maia, 1964- (State University of New York Press, 2006)
"Tainted Milk provides an in-depth analysis of the debate about infant nourishment issues, with a particular focus on environmentally contaminated breastmilk. Maia Boswell-Penc asks why feminists and environmentalists have, for the most part, remained relatively quiet about the fact that environmental toxins have been appearing in breastmilk. She argues that feminists avoid the topic because of their fear of focusing on biological mothering and essentialist thinking, while environmentalists are reluctant to be perceived as fearmongers advocating formula use and contributing to public hysteria. Boswell-Penc also points to the continuing racism, classism, ageism, and corporatization that leaves the less privileged among us more vulnerable."--Jacket